Avaliação de implantação do Núcleo de Estimulação Precoce (NEP), para o atendimento às crianças com síndrome congênita do Zika vírus (SCZ), na área descentralizada de saúde (ADS) de Sobral - Mourão, Bruna Maria Osterno (2023)
In 2015, after the sudden increase in the number of cases of microcephaly in Brazil, the Brazilian Ministry of Health associated this malformation with vertical transmission of the Zika virus. In 2016, a State of International Public Health Emergency was declared by the World Health Organization. In Ceará, the Health Secretariat designated six hospitals and polyclinics, from the 5 macro-regions, to receive suspected cases and subsequent referral for the necessary interventions. This research was developed descriptively with a qualitative methodological approach, centered on Evaluative Research. The research took place at the Bernardo Félix da Silva Polyclinic, at the Precocious Stimulation Nucleus, in Sobral. Professionals and managers who work in the NEP were selected, as well as mothers/caregivers of children with microcephaly. The analysis of 06 medical records of children who were undergoing therapeutic follow-up in the second half of 2021 and the panel of NEP indicators from July to September 2021 were carried out. Semi-structured interviews were carried out with 03 professionals in the category Physical Therapy, Speech Therapy and Social Worker; 04 mothers of children treated at the service and 01 Polyclinic manager. In the treatment of information, a grouping with categorization of speeches was carried out. For the Implementation of the NEP, with significant reports for the interviewees, due to the access to health that the children started to receive; Weaknesses and Potentialities of the NEP, citing infrastructure, ease of scheduling appointments, fragility for bids for materials and hiring of new professionals, as well as the continuity of technical-scientific support from the Center for Treatment and Early Stimulation; Socioeconomic profile of children with Microcephaly assisted in the NEP, evidenced the lack of work on the part of the mothers, as they were fully dedicated to the care of the children, also showing the importance of the BPC, their precarious educational conditions, as well as health care; Operationalization of the NEP, corroborating with the coordination and ordering of primary care, for the due referrals for marking/scheduling in the NEP, and Therapeutic Accompaniment in the NEP, was, in short, evaluated by all respondents as a step forward for the neuropsychomotor development of children in consultations, even with smaller numbers and time per age group of consultations that mothers request, with an improvised physical space, however, welcoming and spacious for the demand. It is still necessary to think about improvements and advances for this population, such as an increase in services within the health network, mainly for new syndromes and/or autism spectrum disorder, the importance of having permanent education for professionals, the need for hiring or competition public with salaries compatible with the market. Financing for the service to be expanded, thinking about a form of health care for mothers/caregivers, work, income and leisure. Another factor that is veiled is the basic education of this population, the difficulty of enrolling and keeping in school. Quality healthcare transport with a more strategic waiting time for coming and going.